The Effect Partnership on Performance Small and Medium Enterprises based Law No.9 of 1995 in Tebing Tinggi City - Hulu, Fonaha (Budapest International Research and Critics University, 2021)
This study examines the effect of partnership on the performance of small and medium businesses in Tebing Tinggi City. the research method description analysis using a qualitative research approach, data collection through interviews and literature. Based on law number 9 of 1995 article 1 paragraph 8